Whose goals? Whose aspirations? : learning to teach underprepared writers across the curriculum - Fishman, Stephen M. (Utah State University Press, 2002)
Ever since Horace Mann promoted state supported schooling in the 1850s, the aims of U.S. public education have been the subject of heated national debate. Whose.